The Contextual Effect of Village on Health Preventive Behavior for Dengue Hemorrhagic Fever in Pati, Central Java - Nurul Fatimah; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2019)
Background: Dengue is a mosquito-borne infection that has emerged to become a major public health issue and can result in death. Various efforts have been made as an attempt to empower the community in dengue preventive behavior, but has not yet reached the optimal result. This study aimed to examine the effect of the village on the health preventive behavior for dengue hemorrhagic fever in Pati, Central Java.Subjects and Method: This was a case-control study conducted in Pati, Central Java, in November 2018. A sample of 225 household heads was selected by simple random sampling. The dependent variable was DHF preventive behavior. The independent variables were education, access to information, knowledge, attitude, self-efficacy, community health behavior, social capital, and villages. Data on DHF status was measured by medical record. The other data were collected by questionnaire. The data were analyzed by multilevel multiple logistic regression.Results: DHF preventive behavior improved with high education (b= 0.86; 95% CI= 0.04 to 1.70; p= 0.040), good knowledge (b= 0.86; 95% CI= 0.06 to 1.67; p= 0.036), strong self efficacy (b= 0.87; 95 % CI= 0.06 to 1.68; p= 0.036), good access to information (b= 1.98; 95% CI= 1.06 to 2.87; p <0.001), positive attitude (b= 1.40; 95% CI= 0.55 to 2.25; p= 0.001), good community behavior in DHF prevention (b= 0.86; 95% CI= 0.02 to 1.70; p= 0.045), and strong social capital (b= 1.07; 95% CI= 0.26 to 1.89; p= 0.010). Village had strong contextual effect on DHF prevention behavior with ICC= 20.30%.Conclusion: DHF preventive behavior improves with high education, good knowledge, strong self-efficacy, good access to information, positive attitude, good community behavior in DHF prevention, and strong social capital. The village has a strong contextual effect on DHF prevention behavior.Keywords: dengue hemorrhagic fever, preventive behavior, village, multilevel analysisCorrespondence: Nurul Fatimah. Masters Program in Public Health.Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nurul.fatimah00049@gmail.com. Mobile: +6281329501844.Journal of Epidemiology and Public Health (2019), 4(3): 198-204https://doi.org/10.26911/jepublichealth.2019.04.03.07